2020
DOI: 10.1111/irv.12789
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses in pediatric emergency department patients and their family members

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…After the COVID-19 pandemic, the public was encouraged with the wearing of masks, regular hand washing and frequent disinfection, which greatly reduced the transmission of respiratory pathogens. In this study, we found that the highest positive rate of pathogen detection was HRV, which was consistent with the results of other studies 17 . However, there was no significant different of RSV detection rate compared with 2019.…”
Section: Discussionsupporting
confidence: 93%
“…After the COVID-19 pandemic, the public was encouraged with the wearing of masks, regular hand washing and frequent disinfection, which greatly reduced the transmission of respiratory pathogens. In this study, we found that the highest positive rate of pathogen detection was HRV, which was consistent with the results of other studies 17 . However, there was no significant different of RSV detection rate compared with 2019.…”
Section: Discussionsupporting
confidence: 93%
“…After the COVID-19 pandemic, the public was encouraged with the wearing of masks, regular hand washing and frequent disinfection, which greatly reduced the transmission of respiratory pathogens. In this study, we found that the highest positive rate of pathogen detection was HRV, which was consistent with the results of other studies [17]. However, there was no signi cant different of RSV detection rate compared with 2019.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have suggested that mixed detections may lead to more severe outcomes, whereas others have not found this association 15 . Our study identified mixed detections in 3.1% of the tested samples, with RV being the most frequently detected virus in these cases, consistent with previous studies 13,14 …”
Section: Discussionsupporting
confidence: 90%